IbM Kelurahan Candirejo dalam Penataan Pencatatan dan Pelaporan Posyandu - Afriyani, Luvi Dian; Veftisia, Vistra; Khayati, Yulia Nur (Jurnal Pengabdian Dharma Bakti, 2019)
Public health data is needed to determine the health activity plan in accordance with the problems and needs of the community. This data can be used as the initial information of health problems, so the solution to resolve it can be found. Posyandu in Candirejovillage is routinely implemented and supported by active cadre, but the record is still not in accordance with the guidance of Posyandu recording, so that data has not been maximally reported. The purpose of this activity is to provide the knowledge and improving cadre skills in carrying out the record and Posyandu report. The benefits of this service are able to make arrangement in accordance with the guidelines of the Posyandu’srecord and reporting. This activity will be implemented in 3 stages. The first stage is refreshing cadre,which will be followed by 20 cadre from 5 Posyandu in Candirejovillage. Recording and reporting assistance and monitoring and evaluation. Instrument that will be used are pre and post Questionnaires, knowledge exam of recording and reporting, and alsoPosyandu’s recording format as well. The result of this refreshing cadre activity is to increasing cadre knowledge, so that cadre is able to do the recording, according to the guiding program. The cadre could be recording each new target data completely, and dividing the task between the cadre in Posyandu recording and reporting.Keywords : Posyandu, recording,reporting